Wisdom, intelligence, and creativity synthesized - Sternberg, Robert J. (Cambridge University Press, 2003)
Sternberg argues that any serious understanding of intelligence must go beyond the standard paper and pencil tests currently in use. Understanding one's intellectual shortcomings, and learning how to overcome, is as important as developing one's strengths.